Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar Matematika pada Materi Bangun Datar di Kelas IV Sekolah Dasar - Oktoria, Putri; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This researchaims to determine the effect of cooperative learning model jigsaw on learning outcomes in the wake of material flat in the fourth grade primary school. This type of research is quasy experimental design. The design used Nonequivalent pretest-posttest control group design. The sampling technique is simple random sampling, where the population is Cluster II district. Lubuk Kilangan Padang. The study was conducted at SDN 01 IVA class Bandar Create as experimental class and class IVA SDN 09 Bandar Create a control class. The data were analyzed using t-test, with the results of the acquisition of t hitung > t table with 4.372> 2.002. It can be concluded that cooperative learning model jigsaw positive effect on the learning outcomes of students in the wake of material flat in the fourth grade primary school.Keywords: Model jigsaw cooperative learning, learning outcomes.